11 The Decennial Relationship between Heart Failure and Atrial Fibrillation – A Large Population Study. (3rd June 2016) - Rasoul, D; Ziaei, F; Shan, SKA; Khan, J; Bhayani, R; Shakir, S; Uppal, Hardeep; Chandran, S; Sarma, J; Potluri, Rahul
Abstract : Introduction: Heart Failure (HF) is common in the western world, has multiple causes and confers significant morbidity and mortality. It is thought a significant proportion of HF patients also have atrial fibrillation (AF) although data from a large population in the UK are lacking. We studied the prevalence of AF in patients with HF in the North West of England. Methods: Anonymous data of adult patients aged ≥ 18 with HF and AF attending seven hospitals between 2000–2013 was obtained and processed using the ACALM (Algorithm for Co-morbidity, Associations, Length of stay and Mortality) study protocol. ACALM uses the ICD-10 and OPCS-4 coding systems to identify patients and the data was analysed in SPSS. Results: Of 929, 465 adult patient population there were 31, 760 (3.4%) patients with HF. Mean age 73.6 years with a male population of 50.3%. Of these 10, 992 (34.6%) patients had AF. The prevalence of AF in patients with HF increases with age from 8.1% in the 30–39 year age group to 42.4% in the 80–89 years group (See Table 1 ). Conclusion: Whilst a significant number of elderly patients with HF patients do have concurrent AF, we found that the majority of patients do not. We believe our findings are important to appreciate whilst optimising heart failure medications in elderly patients.